WIARA I ROZCZAROWANIE W CYWILIZACJI KONSUMPCYJNEJ - Golka, Marian (Wydział Prawa i Administracji UAM, 2004)
The system of values, attitudes and behaviours related to consumption is becoming a collection of key determinants and conditions of contemporary people’s lives, becoming their most profound faith and their most painful disappointment. All individual buyers have the faith, or at least conviction, that purchasing more and more new goods, if hardly useful or altogether useless, will contribute to their happiness or, which need not mean the same, will relieve them from pain. They also have the faith that the fate of civilisation in founded upon consumption by the principle of chain of mutual relations: consumption-demand-production - economic growth-social peace. These two types of faith have some characteristics of quasi-religious doctrine. Most people, whether openly or secretly, deeply believe that individual and collective happiness depends on consumption. Like any other faith, also this one brings disappointment due to disproportionate needs as well as excessive opportunities to satisfy one’s needs outgrowing the needs that one really feels. The disappointment becomes yet more acute due to conflicting needs (e.g. physiological and social needs) and the rapidity of occurrence of new needs before the tension is released following the satisfaction of the previous need. Additionally, there are aspirations, obligations and claims that one pursues as a result of social pressures, although they would otherwise seem utterly foreign to him.
FAITH AND DISAPPOINTMENT IN CONSUMERIST SOCIETY